Efficiency Analysis in the Ghana’s Banking Industry - OSEI , Victor (Asian Journal of Empirical Research, 2013)
This study attempted to investigate the level of Bank efficiency in Ghana by using Data Envelope Analysis (DEA). The study revealed that bank efficiency in Ghana has improved after the introduction of financial sector reforms in 1988 which have led to more competitions among banks, increased financial innovation, strict regulatory regime and higher profitability. The operational, technical and management efficiencies of the Ghanaian banks have significantly trended up as a result of improved corporate governance, regulatory environment and state of the art banking infrastructure and sustained macroeconomic stability over the study period.